Revolusi 5G: bagaimana jaringan seluler generasi kelima mengubah dunia digital - Habibah, Alifiyah Nur (Maliki Interdisciplinary Journal, 2024)
The 5G technology revolution marks a new era in mobile communications, offering high speeds, low latency and greater capacity than previous generations. With the ability to achieve download speeds of up to 20 Gbps and support for up to 1 million devices per square kilometer, 5G is expected to accelerate digital transformation in various sectors, including health, education and industry. Although this enormous potential can improve people’s quality of life and create new business opportunities, 5G implementation also faces significant challenges, such as high infrastructure costs, data privacy and security issues, and inadequate regulations. Therefore, it is important for governments and telecommunications operators to invest in infrastructure, establish supportive regulations, and increase public awareness about this technology. With the right approach, the benefits of 5G can be felt equally by all levels of society, encouraging innovation and economic growth in an increasingly advanced digital era.